The Constitution understood as law - Casanova, Carlos A. (Derecho Público Iberoamericano, 2020)
This paper deals with the nature of the Constitution. It concludes that the Constitution is Law in the sense in which this word “Law” was understood in classical philosophy. It is a Law to which the people as a whole is subject. Its nature is not in essence that of a pact even if it may have some contractual elements. The paper also concludes that the Constitution is not the founding event of a republic. The Constitution presupposes a pre-constitutional juridicity. The paper examines, moreover, what the nature of such juridicity is and adheres to the classical view, rejecting the Lockean views (both liberal and utilitarian), the Kantian view and the Marxist view.